ADP-Ribosylation Factor-Like 2 (ARL2) regulates cilia stability and development of outer segments in rod photoreceptor neurons. Issue 1 (December 2018) - Wright, Zachary; Loskutov, Yuriy; Murphy, Daniel; Stoilov, Peter; Pugacheva, Elena; Goldberg, Andrew; Ramamurthy, Visvanathan
Abstract Photoreceptor cells are specialized neurons with a sensory cilium carrying an elaborate membrane structure, the outer segment (OS). Inherited mutations in genes involved in ciliogenesis frequently result in OS malformation and blindness. ADP-ribosylation factor-like 2 (ARL2) has recently been implicated in OS formation through its association with Binder of ARL2 (BART or ARL2BP), a protein linked to inherited blinding disease. To test the role of ARL2 in vision we created a transgenic mouse model expressing a tagged-dominant active form of human ARL2 (ARL2-Q70L) under a rod-specific promoter. Transgenic ARL2-Q70L animals exhibit reduced photoreceptor cell function as early as post-natal day 16 and progressive rod degeneration. We attribute loss of photoreceptor function to the defective OS morphogenesis in the ARL2-Q70L transgenic model. ARL2-Q70L expression results in shortened inner and outer segments, shortened and mislocalized axonemes and cytoplasmic accumulation of rhodopsin. In conclusion, we show that ARL2-Q70L is crucial for photoreceptor neuron sensory cilium development. Future research will expand upon our hypothesis that ARL2-Q70L mutant interferes with microtubule maintenance and tubulin regulation resulting in impaired growth of the axoneme and elaboration of the photoreceptor outer segment.